Cokriging of transmissivity from head measurements revisited in the case of two quasi steady state flows - de Fouquet, Chantal; Nos, Jérémy (Comptes Rendus. Géoscience)
The theoretical relationships between simple and cross-covariances of the transmissivity and the hydraulic head, deduced from the linearisation of the flow equation are used for cokriging transmissivity field with data from one then two quasi steady-state flows. First a non-exhaustive historical review of geostatistical modelling based on flow equations in a simplified case is given. Then original results show that the estimation of the logtransmissivity by cokriging with head data from two flows is improved compared with the case of head data from a single flow. The estimation in the presence of a transmissivity barrier is thoroughly investigated. Practical conclusions are drawn and perspectives based on the recent numerical variogram are proposed.